2005
DOI: 10.1017/s0959259805001723
|View full text |Cite
|
Sign up to set email alerts
|

Measuring loneliness in later life: a comparison of differing measures

Abstract: The social environment is one of the key factors determining the quality of life of older people. Research has consistently demonstrated a strong and positive relationship between social engagement in all forms but especially participation within kin and wider social networks, and a high quality of life. However, this recognition of the importance of this relationship is not new. In the early 1960s, the ‘activity theorists’ of aging posited that the key to a good old age was the maintenance of high levels of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 12 publications
11
135
1
5
Order By: Relevance
“…Direct and indirect measures of loneliness present a somewhat different picture of loneliness and the characteristics of lonely people (Shiovitz-Ezra and Ayalon 2012). Single-item measurements referring explicitly to loneliness are commonly used, especially in epidemiological studies, and have been found to be a valid way to measure loneliness (Victor et al 2005).…”
Section: Lonelinessmentioning
confidence: 99%
“…Direct and indirect measures of loneliness present a somewhat different picture of loneliness and the characteristics of lonely people (Shiovitz-Ezra and Ayalon 2012). Single-item measurements referring explicitly to loneliness are commonly used, especially in epidemiological studies, and have been found to be a valid way to measure loneliness (Victor et al 2005).…”
Section: Lonelinessmentioning
confidence: 99%
“…Similarly, higher levels of loneliness have been identified when aggregate measures or scales have been used compared with more "direct", self assessment measures (eg, asking people to rate the frequency of their loneliness on a scale from "always" to "never"). 29,30 In an analysis of data from UK and Australian research, Victor, Grenade and Boldy 29 found that although rates of "severe" loneliness were comparable for both types of measure used , the loneliness scale also revealed higher levels of "moderate" loneliness (assumed as broadly equivalent to "sometimes" lonely on the self-rating scale). This suggests that some older people may be more reluctant to admit directly to being lonely, unless it is quite obvious or severe.…”
Section: Community Settingsmentioning
confidence: 99%
“…According to Weiss's (1973) classic definition, loneliness consists of both social and emotional dimensions, which are inevitably affected by cultural context (Beal, 2006;Gierveld, 1998;Victor, Grenade, & Boldy, 2005).…”
Section: Introductionmentioning
confidence: 99%